2016
DOI: 10.1016/j.biomaterials.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immunotherapy of SM5-1 in hepatocellular carcinoma by conjugating with gold nanoparticles and its in vivo bioluminescence tomographic evaluation

Abstract: SM5-1 is a humanized mouse monoclonal antibody, targeting an over-expressed membrane protein of approximately 230 kDa in hepatocellular carcinoma (HCC). SM5-1 can be used for target therapy in hepatocellular carinoma due to its ability of inhibiting cell growth and inducing apoptosis. However, the tumor inhibition efficacy of SM5-1 in HCC cancer treatment remains low. In this study, we synthesized SM5-1-conjugated gold nanoparticles (Au-SM5-1 NPs) and investigated their anticancer efficacy in HCC both in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…142 The membrane protein is specifically expressed on HCC, melanoma, and breast cancer cells, indicating that it is a promising binding site of NPs for diagnosis and therapy of HCC. [143][144][145] Kou et al 146 fabricated negatively charged PTX-loaded poly(lactide-co-glycolide) (PLGA) NPs and then successfully coated them with cationic polypeptide polylysine fused to SM5-1 single-chain antibody (SM5-1 scFv), which was derived from SM5-1 mAb. The results demonstrated that the nanosystem retained high specific affinity to SM5-1 binding protein and could induce specific and efficient death of SM5-1 binding protein-positive Ch-hep-3 cells.…”
mentioning
confidence: 99%
“…142 The membrane protein is specifically expressed on HCC, melanoma, and breast cancer cells, indicating that it is a promising binding site of NPs for diagnosis and therapy of HCC. [143][144][145] Kou et al 146 fabricated negatively charged PTX-loaded poly(lactide-co-glycolide) (PLGA) NPs and then successfully coated them with cationic polypeptide polylysine fused to SM5-1 single-chain antibody (SM5-1 scFv), which was derived from SM5-1 mAb. The results demonstrated that the nanosystem retained high specific affinity to SM5-1 binding protein and could induce specific and efficient death of SM5-1 binding protein-positive Ch-hep-3 cells.…”
mentioning
confidence: 99%
“…The most refractory limitation in the early detection and prevention of HCC is the absence of symptoms (22). Therefore, an increasing number of studies have focused on identifying novel biomarkers, which can be used to diagnose and prevent HCC in the early stage (23,24). …”
Section: Discussionmentioning
confidence: 99%
“…Ma et al synthesized SM5‐1‐conjugated Au NPs (Au‐SM5‐1 NPs) and investigated their anticancer efficacy in hepatocellular carcinoma. Compared with SM5‐1 alone, Au‐SM5‐1 NPs significantly inhibited tumor growth of both subcutaneous and orthotopic hepatocellular carcinoma tumor models . Taken together, Au NPs‐based vaccines are promising nanocarriers for the delivery of TAAs and may act as an alternative self‐adjuvant.…”
Section: Nps’ Structures For Cancer Immunotherapymentioning
confidence: 91%